Procedurs of Pizzle Rot Treatment in Etawa Goats - Benardin Ariani Nurvijayanti; Dony Chrismanto; Herry Agoes Hermadi; Siti Eliana Rochmi; Agung Budianto Achmad (Journal of Applied Veterinary Science And Technology, 2026)
Background: Goats are widely raised due to their lower maintenance costs compared to cattle. The Etawa crossbreed is one of the most common goat breeds in Indonesia. Pizzle rot is a reproductive disorder in bucks characterized by inflammation and swelling of the penis and prepuce, often associated with dietary factors and secondary bacterial infection. Purpose: To describe the surgical treatment and postoperative management of pizzle rot in a buck. Case(s): A 1.5-year-old Etawa crossbreed buck was presented to the Veterinary Clinic with a history of anorexia and penile swelling. Clinical examination of the reproductive system revealed marked swelling of the penis and prepuce consistent with pizzle rot. Case Management: Surgical treatment was performed by excising the abscessed tissue and removing the urethral obstruction. The affected preputial area was opened, the abscess tissue was removed, and the urethral passage was cleared. Postoperative care included routine wound cleaning, medication administration, and regular monitoring of wound healing. Clinical improvement was observed within a few days after surgery, indicated by reduced swelling and improved urination. The healing process progressed well, and complete restoration of normal penile function was achieved within eight weeks. The buck regained the ability to protrude the penis and urinate normally without recurrence of swelling. Conclusion: Surgical excision of abscessed tissue combined with appropriate postoperative wound care was effective in treating pizzle rot in this buck. Early surgical intervention and proper postoperative management contributed to rapid clinical improvement and complete recovery of penile function.